Esthetic Management of a Discolored Permanent Tooth with Open Apex Using Nonsurgical Retreatment and Bio-Obturation - Vidula Vikas Jain; Neha S Dhaded; Anjali R Dhamale (Oral Sphere Journal of Dental and Health Sciences, 2025)
Background: Traumatic injuries to anterior teeth often result in pulpal necrosis and incomplete root development, posing challenges for both endodontic and esthetic rehabilitation. Traditional apexification methods have evolved with the advent of bioceramic materials, which now allow for more predictable outcomes. In addition, patient esthetic expectations necessitate an integrated approach combining both restorative and cosmetic procedures. Case Presentation: A 20-year-old female presented with a discoloured and previously traumatized maxillary right central incisor (#11), which had undergone failed root canal treatment and exhibited an open apex. Clinical and radiographic examinations revealed periapical pathology and an inadequately obturated canal. Nonsurgical endodontic retreatment was initiated, followed by apexification using MTA to establish an apical barrier and BIO-C repair for complete Bio-obturation. Subsequent internal bleaching was performed to address intrinsic discoloration, and the final esthetic outcome was achieved with an indirect composite veneer. Follow-up visits confirmed resolution of periapical pathology and satisfactory esthetics and function. Conclusion: This case demonstrates that a stepwise, minimally invasive approach involving endodontic retreatment along with bioactive material-based apexification, internal bleaching, and conservative restorative techniques can successfully manage complex cases involving open apices and anterior tooth discoloration. The preservation of natural tooth structure and restoration of esthetics are achievable with careful planning and execution.